Penerapan Media Podcast Untuk Meningkatkan Minat Belajar Mahasiswa Pendidikan Agama Islam - Latifatuz Zahra; Syarnubi; Sukirman; Syarifuddin Zuhri (PAI RAFAH, 2025)
The low interest of students in participating in learning activities motivated this research. Lack of student participation in discussions or asking questions has an impact on decreasing interest in learning. This factor is not only related to education, but also influenced by student behavior, suitability of materials, and teaching methods that do not match their interests and learning styles. Podcast media is an effective educational option. The purpose of this study was to determine the effect of podcast media on learning interest of Master of PAI students class of 2023 UIN Raden Fatah Palembang. This study involved 31 PAI students of class E. A quantitative approach with a pre-experimental design (one-group pre-test and post-test) was used to collect data to measure changes in learning interest. The analysis results showed that the podcast effectively increased students' interest in learning. Before the treatment, 9 students (29%) had high interest, 19 students (61.2%) had moderate interest, and 6 students (19.4%) had low interest. However, after the treatment, students who had low interest dropped to 16 students (52%). With a significance value of 0.001 (p < 0.05), the statistical analysis showed a significant difference between before and after the treatment.